Minitab hand book - Ryan, Barbara F (Duxbury, 2001)
Written by the President of MINITAB, Inc., Barbara Ryan, and Brian Joiner, this text shows by example and step-by-step instruction how to use MINITAB (Versions 12 and 13) to explore and analyze data. The book successfully introduces readers to MINITAB software while teaching them statistics at the same time. The authors not only instruct the students on how to use the software, but they also illustrate why they do things and how things work.